MODIFICATION OF VOWELS IN CONNECTED SPEECH - Teshaboyeva Nafisa Zubaydulla qizi,; Ne`matova Marjona G`ayrat qizi, (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation:The phenomena of vowel modification in connected speech is examined in this article. It looks at how vowels alter their articulation or quality when speaking quickly and fluidly, with an emphasis on elision, reduction, and assimilation. Linguists and language learners alike must comprehend these changes in order to enhance spoken fluency and listening comprehension.